Peran Analisis Jabatan, Evaluasi Jabatan dan Motivasi dalam Meningkatkan Kinerja Pegawai - Eko Budianto; Abadi Sanosra; Ni Nyoman Putu Martini G; Nurul Qomariah (BUDGETING : Journal of Business, Management and Accounting, 2023)
Employee performance is an indicator of organizational performance. If employee performance is good, indirectly the organization's performance will also be good. The aim of this research is to determine and test the impact of job analysis, job evaluation and work motivation on employee performance at the Bondowoso Regency Regional Secretariat. All 61 employees at the Bondowoso Regency Regional Secretariat were used as the population and also the research sample. To describe respondents, descriptive analysis is used. To test the research questionnaire, validity and reliability test analysis was used. Structural Equation Model (SEM) with WarpPLS 5.0. used as a tool to test research hypotheses. The findings from this study are that the employee position analysis variable has a significant effect on employee performance. Job evaluation variables have a significant effect on employee performance. Variable work motivation has a significant effect on employee performance. Keywords: Employee Performance, Job Analysis, Job Evaluation, Work Motivation.